“Reassurance that you're doing okay, or guidance if you're not”: a qualitative descriptive study of pregnant first time mothers’ expectations and information needs about postnatal care in England - McLeish, J; Harvey, M; Redshaw, M; Alderdice, F (Elsevier, 2020)
Objective To explore what first time mothers in England expect from postnatal care while they are pregnant, what they would ideally like, where they get their information on postnatal care, and their views on the sufficiency of this information. Design A qualitative descriptive interview-based study. Setting England Participants A maximum variation sample of 40 women who were currently in the third trimester of pregnancy; aged 16 or over; planning to give birth in England and had not given birth previously. Methods Semi structured interviews were carried out between October 2017 and March 2018, by telephone (n = 32) and face to face (n = 8). Interviews were analysed using thematic analysis. Results There were six themes and twelve subthemes. The themes were: (1) ‘Piecing together snippets of information’ containing subthemes ‘Incomplete official sources’ and ‘Other mothers’ stories’; (2) ‘Planning ahead or going with the flow’ containing subthemes ‘Wanting more information’ and ‘Postnatal care not a priority’; (3) ‘Judgement or reassurance’ containing subthemes ‘Real: Being judged’, ‘Ideal: Reassurance and non-judgmental advice’; (4) ‘Focus of care’ containing subthemes ‘Real: A focus on checks and feeding’, ‘Ideal: More focus on mother's wellbeing’; (5) ‘A system under pressure’ containing subthemes ‘Real: Busy midwives, reactive care’, ‘Ideal: Reliable, proactive information’; (6) ‘Deciding about discharge’, containing subthemes ‘Real: Confusion about decision-making’, ‘Ideal: More control over length of hospital stay’. Key conclusions First time mothers’ experience of the transition to parenthood could be improved by antenatal access to comprehensive information about the timing, location, content and purpose of postnatal care. Information should take a woman-centred perspective and cover all settings (hospitals, birth centres, home, community), including the roles and responsibilities of all the professionals who may be involved. Implications for practice Clear and comprehensive information about postnatal care should be provided to all women in ways that are accessible at any stage of pregnancy or the postnatal period. As women pregnant for the first time worry about being judged if they seek professional advice and reassurance postnatally, information about postnatal care should aim to address this.